Reserve price effects in auctions: Estimates from multiple RD designs - Syngjoo Choi; Lars Nesheim; Imran Rasul (Centre for Microdata Methods and Practice (cemmap), 2010)
We present evidence from 260,000 online auctions of second-hand cars to identify the impact of public reserve prices on auction outcomes. To establish causality, we exploit multiple discontinuities in the relationship between reserve prices and vehicle characteristics to present RD estimates of reserve price effects on auction outcomes. Our first set of results show that, in line with the robust predictions of auction theory, an increase in reserve price decreases the number of bidders, increases the likelihood the object remains unsold, and increases expected revenue conditional on sale. Reserve price effects are found to be larger when there are more entrants, and when the reserve price is lower to begin with. Our second set of results then combine these estimates to calibrate the reserve price effect on the auctioneer's expected revenue. This reveals the auctioneer's reserve price policy to be locally optimal. Our final set of results provide novel evidence on reserve price effects on the composition of bidders. We find that an increase in reserve price: (i) decreases the number of potential bidders as identified through individual web browsing histories; (ii) leads to only more experienced and historically successful bidders still entering the auction; (iii) the characteristics of actual winners are less sensitive to the reserve price than those of the average bidder, suggesting auction winners are not the marginal entrant.
Keywords: D44; L11; L62; 330; auctions; regression discontinuity; reserve price; Auktion; Gebrauchtfahrzeug; Preis